The portrait of the underground economy and tax evasion: Descriptive analysis from border region - Aloysius Hari Kristianto; Pramatatya Resindra Widya; Jones Parlindungan Nadapdap (Publisher of Widyagama University of Malang (UWG Press), 2021)
Underground economic activity is a phenomenon that requires special and continuous treatment. This phenomenon is counterproductive to local revenues and is related to corrupt practices and tax evasion. The research was conducted in Bengkayang Regency, West Kalimantan Province, Indonesia. The qualitative phenomenological method was carried out by interviewing underground economic actors such as liquor producers,